2004
DOI: 10.1007/s00125-004-1338-2
|View full text |Cite
|
Sign up to set email alerts
|

Heritability estimates for beta cell function and features of the insulin resistance syndrome in UK families with an increased susceptibility to Type 2 diabetes

Abstract: Aims/hypothesis. The aim of this study was to measure the heritability estimates for metabolic traits and the features of the insulin resistance syndrome in families with an increased genetic susceptibility to Type 2 diabetes. Methods. A total of 811 non-diabetic relatives from 278 pedigrees of northern European extraction in which there was a sib-pair with Type 2 diabetes were recruited and studied at the six Diabetes UK Warren Type 2 diabetes centres. Heritability estimates were calculated, allowing for key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 19 publications
9
71
0
2
Order By: Relevance
“…This is justified under the assumption that heritable precursors of type 2 diabetes will share the same genetic determinants as type 2 diabetes itself. Diabetes-related QTs are heritable in multiple ethnic groups (for examples, see [94][95][96]), and many also predict the subsequent development of diabetes (for examples, see [97][98][99]). In addition, genetic correlation has been demonstrated between type 2 diabetes and some QTs [100] and between various QTs [14, 37, 96, 100-102].…”
Section: Discussionmentioning
confidence: 99%
“…This is justified under the assumption that heritable precursors of type 2 diabetes will share the same genetic determinants as type 2 diabetes itself. Diabetes-related QTs are heritable in multiple ethnic groups (for examples, see [94][95][96]), and many also predict the subsequent development of diabetes (for examples, see [97][98][99]). In addition, genetic correlation has been demonstrated between type 2 diabetes and some QTs [100] and between various QTs [14, 37, 96, 100-102].…”
Section: Discussionmentioning
confidence: 99%
“…Twin [2][3][4][5] and family studies [6][7][8][9][10] support the notion that people who develop type 2 diabetes have a strong genetic predisposition, which may be partly conveyed through genetic effects on insulin resistance. Two twin studies, for instance, showed a significant genetic contribution to insulin sensitivity, assessed by euglycaemic-hyperinsulinaemic clamp with heritability estimates of 37% and 55% [11,12].…”
Section: Introductionmentioning
confidence: 89%
“…Heritability estimates tend to be higher among twins than in extended pedigrees because of greater similarities in early-life environment and behavioural patterns among twins. In family studies, heritability estimates vary widely (8-72%), which may be partly due to ascertainment bias [10,11]. In a study of 89 randomly ascertained pedigrees, in which variance due to childhood household was also measured, the heritability of fasting glucose was 18% after adjustment for age, sex, BMI, and smoking [12].…”
Section: Introductionmentioning
confidence: 99%